Putting Legal Writing on the Tenure Track: One School’s Experience - Christopher, Catherine Martin (Columbia Journal of Gender and Law, 2015)
This Article discusses the statistics behind the gendered segregation of law school faculties, in which women occupy a disproportionate number of legal writing and other low-status positions, while men continue to hold a disproportionate number of tenured faculty positions. The Article explores the rationales for and against converting legal writing faculty to tenure-track, and shares one law school’s experience of doing so. The Article then suggests lessons and approaches that other schools may wish to take in converting their own legal writing faculty to tenure-track positions.